2013
DOI: 10.3109/0142159x.2013.857013
|View full text |Cite
|
Sign up to set email alerts
|

Emergency skills learning on video (ESLOV): A single-blinded randomized control trial of teaching common emergency skills using self-instruction video (SIV) versus traditional face-to-face (FTF) methods

Abstract: SIV is as effective as FTF in teaching and learning basic emergency skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…When we focus on preclass videos, literature comparing videos to lectures is unclear, with some studies favoring videos, and some finding no difference in learning outcomes . In other studies, video groups showed worse learning outcomes, with authors citing reasons including no peer interaction, low compliance with learning plans, and lack of accountability .…”
mentioning
confidence: 99%
“…When we focus on preclass videos, literature comparing videos to lectures is unclear, with some studies favoring videos, and some finding no difference in learning outcomes . In other studies, video groups showed worse learning outcomes, with authors citing reasons including no peer interaction, low compliance with learning plans, and lack of accountability .…”
mentioning
confidence: 99%
“…Groups attended multiplayer virtual technology, seemed to be more efficient applying CPR in scenarios test [30]. In 2014, a study concerning emergency skills teaching, either by learning on video or face-to-face teaching, found no difference in efficacy of both training methods and also equal confidence to both training methods by the participants [31]. In 2015, the use of a platform (Moodle platform) as a pre-sessional phase prior to classroom phase of teaching advanced life support courses was studied.…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare education, simulation has been used as a teaching tool across a large spectrum of healthcare education such as pharmacy (Tofil et al 2010), nursing (Cant & Cooper 2010) and dentistry. Students can learn lifesaving skills such as cardiopulmonary resuscitation (CPR), defibrillation, intubation, (Mohd Saiboon et al 2014) and intraosseous cannulation skills (Bala Krishnian et al 2016). Simulation was also used to teach less invasive skills like phlebotomy, Ryle's tube insertion, intravenous cannulation, or urinary catheter insertion.…”
Section: Introductionmentioning
confidence: 99%